Heavy metal contamination and ecological risk in post-coal mining soils: A geostatistical approach - Suhardianto, Sigit; Hanudin, Eko; Nugroho, Andhika Puspito (Journal of Degraded and Mining Lands Management, 2026)
Open-pit coal mining significantly alters soil geochemistry through heavy metal accumulation, threatening ecosystem health and post-mining rehabilitation. This study assessed spatial distribution, pollution levels, and ecological risks of Pb, Cd, Ni, and Cr in post-mining soils of Bungo Regency, Jambi, Indonesia. Sixty-one topsoil samples (0-20 cm) were analyzed using Atomic Absorption Spectrophotometry (AAS). Data analysis included descriptive statistics, Pearson correlation, Principal Component Analysis (PCA), and Ordinary Kriging interpolation (ArcGIS 10.8). Pollution and ecological risks were evaluated using the contamination factor (Cf) and the Potential Ecological Risk Index (RI). Pb and Ni showed high spatial variability, indicating strong anthropogenic influence. A moderate correlation between Cr and Ni (r = 0.37) suggests shared geogenic sources, while Pb exhibited weak correlations, confirming distinct anthropogenic origins. PCA explained 85.8% of total variance, identifying three components: PC1 (Cr–Ni, geogenic), PC2 (Pb, mining-related contamination), and PC3 (Cd–Ni, mixed sources). Cf values indicated moderate to high contamination (Cf>3) for Ni and Pb at several sites. Most areas exhibited high ecological risk (RI>300), particularly in former excavation and waste disposal zones. This integrated geostatistical approach effectively delineates contamination patterns and supports targeted remediation strategies in tropical post-mining landscapes.